Analysing data using transana software - Abdul Samad, Adlina (Penerbit UTM Press, 2009)
The general principles of Computer Assisted Qualitative Data Analysis (CAQDAS) are concerned with taking a qualitative approach to qualitative data (Lewins and Silver, 2006). A qualitative approach is one where there is a need to interpret data through the identification and possibly among others; coding of themes, concepts, processes, and contexts, in order to build explanations or theories or to test or enlarge a theory. For that reason the researcher in this study had identified Schellens and Valcke (2005) hierarchical structure typology to perform the data analysis to represent higher levels of knowledge construction. Transana was used by the researcher to anaylse data in relation to the study.